Increased Expression of Extracellular Vesicles Is Associated With the Procoagulant State in Patients With Established Rheumatoid Arthritis - Stojanovic, Aleksandra; Veselinovic, Mirjana; Zong, Yanan; Jakovljevic, Vladimir; Pruner, Iva; Antovic, Aleksandra (Frontiers in Immunology, 2021)
This study sought to identify different subpopulations of extracellular vesicles (EVs) in plasma from female patients with established rheumatoid arthritis (RA) in relation to the activation of coagulation and fibrin formation in these patients. Forty women were included in the study, 20 patients and 20 age-matched healthy controls. The mean disease duration in patients was 13.0 (5.0–25.0) years, with medium to high disease activity despite ongoing treatment with low-dose prednisolone and methotrexate. There were no differences between the investigated groups regarding the presence of traditional cardiovascular risk factors. The concentration of phosphatidylserine-positive (PS+) EVs; platelet (CD42a+), leucocyte (CD45+), monocyte (CD14+), and endothelial (CD144+)-derived EVs; and EVs-expressing tissue factor (CD142+), P-selectin (CD62P+), and E-selectin (CD62E+) were determined by flow cytometry analysis. Overall hemostasis potential (OHP) was assessed to follow the hemostatic disturbances, including the parameters for overall coagulation potential (OCP) and overall fibrinolytic potential (OFP). Fibrin clot turbidity was measured together with clot lysis time, and scanning electron microscopy was performed. Increased concentrations of PS+, CD42a+, CD142+, CD45+, CD14+, and CD62P+ EVs were found in plasma from patients with RA compared to healthy controls, and the concentrations of PS+, CD42a+, CD14+, and CD62P+ EVs were positively correlated with the inflammatory parameters in RA patients. Positive correlations were also found between the levels of PS+ and CD42a+ EVs and OCP as well as between the levels of PS+, CD42a+, and CD62P+EVs and OHP. The levels of PS+, CD42a+, CD14+, CD62P+, and CD62E+ EVs were negatively correlated with OFP. Elevated levels of circulating EVs of different cell origins were found in patients with established RA, in relation to the inflammatory burden and coagulation activation in the disease.